PkM MESIN PENGIRIS KERIPIK TEMPE BAGI PENGRAJIN OLAHAN TEMPE DI DUSUN CUNGFO - Eko Yudo; Ariyanto Ariyanto (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
Tempe chips are processed snacks made from tempeh-based ingredients. Therefore, it can support the development of activities in the snack food home business sector, one of which is the flagship product, "Mbok De Tempe Chips" in the cunfo hamlet, Bukit Layang village, Bakam sub-district. There are problems that occur in the home industry for tempe mbok de chips, namely when the tempe slicing process is still manual using a kitchen knife as a tempe slicer. So it takes a long time and the results of the slices or pieces of tempeh produce thin and thick slices of tempeh. This community service (PkM) aims to overcome the problem of slicing tempeh that still uses a kitchen knife with a tempeh slicing machine to facilitate the slicing process. From the implementation method given in the form of a specific target from the implementation of this PkM, it was achieved well in terms of facilitating the process of slicing tempe chips with uniform slices of thickness and thinness of the tempe chips and increasing production yields so as to expand the results of sellers to increase the results and profits of people's income.